Chronic pancreatitis with unilateral pleural effusion: an atypical presentation - Illani Riza; Yap, Yoon Chin; Lo, Zhen Zhen (Galenos Publishing House, 2024)
Pancreatic pleural fistula is a rare complication of acute or chronic pancreatitis. The most prevalent reasons for chest discomfort in this patient were pleural effusion, mediastinal or pleural pseudocyst. A 42-year-old man presented with left pleuritic chest pain and cough. A plain chest X-ray revealed two large suspicious opacities in the left lung. A contrast-enhanced computed tomography thorax and pancreas shows left pleural effusion and features suggestive of chronic pancreatitis. There was peripancreatic collection and pancreatic duct dilatation which communicated with the left pleura, causing left pleural effusion. Pleural fluid samples showed high pleural fluid amylase and albumin. Endoscopic retrograde cholangiopancreatography (ERCP) was done and the pancreatic duct was stented. Repeated ERCP a month later showed no leakage after stent insertion.